FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AUDIT DELAY PADA PERUSAHAAN LIQUID 45 - Ariyanti, Rizky; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to test the influence of company characteristic which is proxy by total assets, profitability, leverage, auditor opinion, and PAF size to the audit delay through financial statement which has been prepared by Liquid 45 Companies which are listed in Indonesia Stock Exchange. The audited financial statement is financial statement has been audited by the auditors. The financial statement has an advantage as the management responsibility to the stockholders and also for the decision making. It is required to find out the financial position, company performance, and changes of financial position. Audit delay is the length of the day which is needed by the auditors to finish the audit task which is measured from the closing date of year book until the audit statement is published.The population of this research has been done by using purposive sampling method at liquid 45 companies which are listed in Indonesia Stock Exchange during 2012-2015 periods and based on the predetermined criteria, 20 companies have been selected as samples. The analysis method has been carried out by using multiple linear regressions analysis and the SPSS. The result of the t test shows that in the analysis factor there are 2 of 5 variables which give influence to the audit delay, i.e. profitability and leverage. Meanwhile, the total assets, auditor opinion, and PAF size do not have any influence to the audit delay.Keywords: Audit delay, profitability, leverage.